Caracterização comportamental endócrina das fases ontogenéticas de sagüi comum (Callithrix jacchus) - Castro, Dijenaide Chaves de (2011)
The use of animal models in biomedical research is ever increasing. Models that use primates might also have advantages in terms of low maintenance costs and availability of biological knowledge, thereby favoring their use in different experimental protocols. Many current stress studies use animal models at different developmental stages since biological response differs during ontogeny. The aims of this study were to perform a detailed characterization of the developmental stages of common marmosets (Callithrix jacchus), a very important animal model used in biomedical research. Ten subjects, 6 females and 4 males, were followed from birth to initial adult age (16 months). Behavioral and fecal collection for measurement of adrenal (cortisol) and sex (progesterone, estradiol and androgens) hormones took place twice a week during the first month of life and once a week for the remainder of the study. Behavior was observed for 30 minutes in the morning (0700-09:00h) and afternoon (12:00-14:00h). Behavioral profile showed changes during ontogeny, characterizing the 4 developmental stages and the respective phases proposed by Leão et al (2009).. Differentiation of developmental stages was considered using the onset, end, change and stabilization of the behavioral profile parental care (weaning and carrying), ingestion (solid food), affiliation (social grooming) and autogrooming, agonism (scent marking and piloerection) and play behavior and endocrine profile. Infant weaning and carrying terminated within the infantile stage and the peak of solid food ingestion was recorded in the infantile III phase. Receiving grooming was recorded earlier than grooming performed by the infant and autogrooming. The first episode of scent marking was recorded in the 4th week and it was the least variable behavior, in terms of its onset, which, in almost all animals, was between the 5th and 7th week of life. Solitary play and play with the twin started around the 7th week and play with other members of the group started 8 weeks later. Sex hormone secretion started to differ from basal levels between the 21st and 23rd week of life, in males and females, suggesting that puberty occurs simultaneously in both sexes. Basal cortisol, even at an early age, was higher in females than in males. However, cortisol was not correlated with the juvenile stage, as expected, since this stage corresponds to the transition between infancy and adult age and most behaviors are intensified by this time. The behavioral and endocrine profile of subadult animals did not differ from that of the adults. These results provide more detailed parameters for the developmental process of C. jacchus and open new perspectives for the use of experimental approaches focused on the intermediate ontogenetic phases of this species